TRANSFORMATION OF THE CULTURAL-COMMUNICATIVE SPACE OF THE MUSEUM IN THE INFORMATION AGE - I. I. Tolstikova (Дискурс, 2017)
The research purpose was to explore transformation of the cultural and communicative space of museums and to evaluate the role of information technologies in expanding the boundaries of museum activities. The information provision is one of the communicative activities of museums and makes it necessary to create new communicative images that can affect the audience taking into consideration socio-demographic and psychological characteristics of visitors. Considering a museum as a form of leisure, we focus on social advantages and significance of the museum for the audience at large. We investigate options of solving the problem of overcoming the conservative aspect of the museum phenomenon through the development of a website as an integrative socio-cultural phenomenon, which allows improving the technologies for involving representatives of various strata of the population in the creative environment of the museum by means of a webpage as an interactive playing and information space.